The Industry of Evangelism - Thomas, Drew B., author.
1 online resource.
Keywords: Of the leading print centres in early modern Europe, Wittenberg was the only one that was not a major centre of trade, politics, or culture. This monograph examines the rise of the Wittenberg printing industry and analyses how it overtook the Empire's leading print centres. It investigates the workshops of the four leading printers in Wittenberg during Luther's lifetime: Nickel Schirlentz, Josef Klug, Hans Lufft, and Georg Rhau. Together, these printers conquered the German print world.